The Comparison between Preoperative Maltodextrine and Sugar Water Administration on Random Blood Glucose Levels in Enhanced Recovery After Cesarean Surgery (ERACS) Patients - Wicaksono, Satrio Adi; Riwanto, Ignatius; Pudjonarko, Dwi (JAI (Jurnal Anestesiologi Indonesia), 2024)
Background: Oral carbohydrate administration reduces post-operative insulin resistance and improves post-operative recovery. Sugar water and maltodextrin are oral carbohydrates that can be given to enhanced recovery after caesarean surgery (ERACS) patients.Objective: To compare the effect between pre-operative maltodextrin treatment and sugar water treatment on random blood glucose (RBG) levels in enhanced recovery after caesarean section (ERACS) patients.Methods: A randomized control study with pre-test and post-test design was used on 48 patients who underwent ERACS surgery at Dr. Kariadi hospital Semarang Indonesia and met the inclusion and exclusion criteria. Study subjects were divided into two groups: a pre-operative maltodextrin treatment group (n=24) and a pre-operative sugar water control group (n=24). RBG levels were checked with point-of-care testing (POCT) at soon before surgery and at 2 hours after surgery. Mann-Whitney test was used to analyse the difference of RBG levels between group with Maltodextrin and group with sugar water. Wilcoxon test was used to analyse the difference of RBG levels before surgery (pre-operative RBG) and 2 hours after surgery (post-operative RBG). The p value of <0.05 was considered as statistically significant.Result: There were significant lower RBG levels in group with pre-operative maltodextrin treatment compared to group with pre-operative sugar water at soon before surgery (pre-operative) (83.5 ± 9.73 vs 96.2 ± 12.99 mg/dL, p=0.003) and at 2 hours post-operative (101.7 ± 15.81 vs 118.9 ± 28.38, p=0.035) in ERACS patients.Conclusion: If confirmed by further studies, pre-operative maltodextrin administration might provide better outcome in reducing post-operative catabolic status by reducing post-operative insulin resistance and improving RBG levels before and after ERACS compared to sugar water control.